The effect of advertising on OTC painkillers consumption: a statistical analysis in the regional unit of Florina, Greece. (10th September 2021) - Kipourou, Vasiliki; Polychronidou, Persefoni
Advertising is considered as an integral part of pharmaceutical marketing, especially today in the world of the huge development of OTC drug market. This study tested the impact of advertising on OTC painkillers consumption in the regional unit of Florina. Self-managing with pain was focused and the tool of the survey was a structured questionnaire. Analysis has shown that OTC painkillers advertising makes the consumers aware of the drug rather than convinces them to purchase it. Doctors' and pharmacists' recommendations and the trust in the OTC analgesic are the main reasons that influence their decision making process. Also, most consumers have moderate attitude about OTC painkillers advertisements and this is reinforced by their moderate level of involvement with these drugs. As a conclusion, advertising cannot be excluded from pharmaceutical marketing, but it should be used as a piece of the great strategic marketing plan.